DETAMAL (ANTI-THEFT DETECTOR) : THEFT CASE PREVENTION DETECTOR APPLICATION OF MICROCONTROLLER ARDUINO UNO BASED AS HOME SECURITY SYSTEM - Ardian, Zalfie; Dewi, Sarini Vita (Universitas Ubudiyah Indonesia, 2016)
The increasing criminal case nowadays makes people worried about losing their properties. In addition, they do not hesitate to act anarchist and often hurt the victim. These criminals frequently come to the victims house to perform the act of theft. However, theft is often successfully thwarted only by a shout or alarm sound that makes the thief to be panic and afraid then run while cancelling his intention toÂ proceed with his action. Therefore the authors wanted to create an automatic detection system by relying on Arduino UNO, PIR sensor as motion detector and equipped with a camera that will capture images right after the sensor sounds and the sound is expected to thwart the robbery action. The advantages of this application is the camera will rotate automatically where the sensors that detect the presence of the thief detected. And the resulting sound is also derived from the micro SD memory card with MP3 format so that the users can use the sound of shouting, guard dog, or siren that will make the thief panic and run.Keywords : arduino uno, detector, pir sensor, theft